3D Modelling approach to identify parametric configurations for pillar stability in underground metal mine: a case study - Abhishek Mehra; G. Budi (Geomatics, Natural Hazards & Risk)
In underground metal mining, ensuring the stability of pillars considered as a principal apprehension, given the likelihood of stress increase and relief leading to dynamic pillar failure. Through a detailed analysis examining stress concentration factor (SCF), deformation and yielding surrounding crown and rib pillars, this study explores the impact of various rock mass parameters. A detailed investigation utilizing non-linear 3D numerical models, governed by Mohr–Coulomb elastoplastic failure criteria, is conducted by manipulating seven variables: working depth (D), uniaxial compressive strength (σci), modulus of elasticity (Em), geological strength index (GSI), crown pillar thickness (TC), rib pillar thickness (TR), and stope width (WS). The findings suggest that increasing D from 230 m level to 290 m level exhibits a 6.62% decrease in major SCF, a substantial 26.37% decrease in minor SCF, and a noteworthy 119.9% increases in yield around crown pillars. Also, at lower depths, the rib pillar experiences a 243.31% increase in yield zone. Present study also exhibits possible failure of pillars in terms of factor of safety (FoS). This study offers crucial insight essential for optimizing pillar design and improving safety of the mine which further benefits industry financially by altering additional operational cost.